An aging giant at the center of global warming: Population dynamics and its effect on CO2 emissions in China. (1st February 2023) - Guo, Hongwei; Jiang, Jia; Li, Yuanyuan; Long, Xinxin; Han, Ji
Abstract: Revealing the complex correlation between population aging and CO2, and projecting their future dynamics are fundamentally necessary to inform effective policies toward a low-carbon and sustainable development in China. Differing from the existing studies, this study highlighted a quantitative investigation on the impact of aging on CO2 emissions across the different stages of regional development in China through a STIRPAT model based on balanced provincial panel data from 1995 to 2019, and projected the demographic change and CO2 emissions till 2050 by employing cohort model and scenario analysis. It is found that CO2 emissions in China has witnessed a significant growth during 1995–2019, and will exhibit an inverted U-shaped growth till 2050 with its peak appears between 2030 and 2040. Statistically, every 1% growth of aging population will cause a 0.62% increase in CO2 emissions in China. However, a big regional difference was also detected as aging contributed to CO2 reduction in the eastern region, but stimulated CO2 emissions in the central and western regions. Policy implications for achieving a low-carbon and aging-oriented sustainable development may include the integration of aging into the decision-making in industrial structure upgrading and CO2 emission reduction at both national and region levels, the promotion of further transition to low-carbon consumption and green products in the eastern region, and strengthening the deep fusion of aging-oriented industries with local resource and environmental endowment in the central and western regions such as the development of eco-agriculture and green pension industries. Highlights: Correlation between aging and CO2 emissions in China was examined. 1% increase of aging will exert a 0.62% upward pressure on CO2 emissions in China. Future changes of demography and CO2 emissions till 2050 was projected. Effect of aging on CO2 emissions was different cross China regions. Policy implications for low-carbon and aging-oriented development were proposed.